Characterization of printed PLA scaffolds for bone tissue engineering. Issue 4 (20th November 2017) - Grémare, Agathe; Guduric, Vera; Bareille, Reine; Heroguez, Valérie; Latour, Simon; L'heureux, Nicolas; Fricain, Jean‐Christophe; Catros, Sylvain; Le Nihouannen, Damien
Abstract: Autografts remain the gold standard for orthopedic transplantations. However, to overcome its limitations, bone tissue engineering proposes new strategies. This includes the development of new biomaterials such as synthetic polymers, to serve as scaffold for tissue production. The objective of this present study was to produce poly(lactic) acid (PLA) scaffolds of different pore size using fused deposition modeling (FDM) technique and to evaluate their physicochemical and biological properties. Structural, chemical, mechanical, and biological characterizations were performed. We successfully fabricated scaffolds of three different pore sizes. However, the pore dimensions were slightly smaller than expected. We found that the 3D printing process induced decreases in both, PLA molecular weight and degradation temperatures, but did not change the semicrystalline structure of the polymer. We did not observe any effect of pore size on the mechanical properties of produced scaffolds. After the sterilization by γ irradiation, scaffolds did not exhibit any cytotoxicity towards human bone marrow stromal cells (HBMSC). Finally, after three and seven days of culture, HBMSC showed high viability and homogenous distribution irrespective of pore size. Thus, these results suggest that FDM technology is a fast and reproducible technique that can be used to fabricate tridimensional custom‐made scaffolds for tissue engineering. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 887–894, 2018.